Simultaneous Estimation of Metoprolol Succinate and Olmesartan Medoxomil in Pharmaceutical Formulation by Thin-Layer Chromatographic-Densitometric Method. (27th June 2012) - Baldania, Sunil L.; Parmar, Ankit B.; Bhatt, Kashyap K.; Shah, Dimal A.; Chhalotiya, Usmangani K.
Abstract : A new, simple, accurate, and precise high-performance thin-layer chromatographic (HPTLC) method is described for simultaneous analysis of metoprolol succinate and olmesartan medoxomil in pharmaceutical formulations. The separations were achieved on prepared TLC plates precoated with silica gel G 60 F254 and the plates were developed with methanol-ethyl acetate-toluene-glacial acetic acid 2.5 : 3 : 4.5 : 0.3%v/v/vas mobile phase. Detection and evaluation of chromatograms were performed densitometrically at 224 nm. The retention factor of metoprolol succinate and olmesartan medoxomil was 0.25 and 0.70, respectively. The linear range was 1000–2250  η g per spot for metoprolol succinate and 800–1800  η g per spot for olmesartan medoxomil and the correlation coefficients ( r ) were 0.993 and 0.999, respectively. The method was validated for linearity and range, specificity, precision, accuracy, and robustness, and the results were found to be within the acceptance criteria. The method was successfully applied to the analysis of drugs in their capsule dosage form.